2021
DOI: 10.37741/t.69.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Mapping the Evolutionary Phases of Tourism Area Life Cycle (TALC)

Abstract: This paper aims to simulate the stages of the Tourism Area Life Cycle (TALC) in Goa, India, based on the number of tourist arrivals and tests whether the stages correspond with the stages of TALC as predicted in the theory. The graphs are plotted for total, foreign, and domestic tourists from 1962-2018. A compliance assessment of the indicators with the TALC stages is also done to ascertain the extent of development. The leading indicators of the exploration, stagnation, and decline stages are identified. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…Even though all the areas are taken into consideration, there are still ways to go to achieve economic vitality because there is not much evidence of sustainable economic development of the destination. This will also depend on the lifecycle of the tourism products in any given destination (Gore et al 2021). It is the results of continuous natural calamities, such as the floods in 2017 and 2018, and the landslides due to heavy rain.…”
Section: Discussionmentioning
confidence: 99%
“…Even though all the areas are taken into consideration, there are still ways to go to achieve economic vitality because there is not much evidence of sustainable economic development of the destination. This will also depend on the lifecycle of the tourism products in any given destination (Gore et al 2021). It is the results of continuous natural calamities, such as the floods in 2017 and 2018, and the landslides due to heavy rain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research (Dodds, 2020;Gore & Borde, 2021;Javed & Tučková, 2020;Lee & Weaver, 2014) it can be concluded that tourist village life can use the life cycle approach of tourist areas with the results of previous research conveying solutions for tourism village managers by designing product rejuvenation strategies, including visitor Management by limiting the number of tourist visits can provide early warning if the visit is Tourists have exceeded the maximum limit that has been determined and changed their orientation from the previous business based on quantity to quality.…”
Section: Tourism Area Life Cyclementioning
confidence: 98%
“…Butler (2022) and McKercher and Wong (2021) proposed analysing tourist destinations as a single product. Most scholars recommend utilising the TALC model to map tourism development and evaluate strategies at a tourist destination (Gore et al , 2021a, b; Marsiglio and Tolotti, 2022; Nazneen et al , 2020). In addition, scholars suggest understanding the role of the government, entrepreneurs and regulations in shaping the destination (Javed and Tučková, 2020; Szromek, 2019; Weaver et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents the criteria for identifying the stages of TALC. Gore et al (2021a) identified the stages based on the criteria and evaluated the tourism development indicators for each stage of the TALC. The literature reviews on TALC discussed its applicability, methodology, unit of analysis, variables and research problems (Gore et al , 2022; Lagiewski, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation